Comparative morphology of myrmecophilous immature stages of European Microdon species (Diptera: Syrphidae): updated identification key and new diagnostic characters - Scarparo, Giulia; Wolton, Robert; Molfini, Marco; Pinna, Luigi Cao; Giulio, Andrea Di (Zootaxa, 2020)
Hoverflies (Diptera: Syrphidae) of the genus Microdon Meigen have larvae that live in ant nests where they are predatory on ant larvae. Reflecting the exceptional challenges of this very specialized lifestyle, Microdon eggs, larvae and puparia are highly distinctive in their morphology. Detailed descriptions of these immature stages is, however, lacking for all but a very few species, and much of this has been limited through the sole use of light microscopes. Here, using Scanning Electron Microscopy (SEM), we present detailed, comparative descriptions of the immature stages of three European Microdon species: M. analis, M. devius and M. myrmicae. Given that many adult Microdon species are very similar to each other in their outward appearance, we demonstrate that the morphology of their immature stages can improve our understanding of the phylogeny of the genus. We also discuss how particular adaptations of the immature morphology may allow their myrmecophilous life within ant nests. In this paper new diagnostic features are also presented to distinguish M. myrmicae from its sibling species M. mutabilis—the two are morphologically indistinguishable as adults.